Increased monocyte turnover is associated with interstitial macrophage accumulation and pulmonary tissue damage in SIV‐infected rhesus macaques. Issue 6 (16th March 2015) - Cai, Yanhui; Sugimoto, Chie; Liu, David Xianhong; Midkiff, Cecily C.; Alvarez, Xavier; Lackner, Andrew A.; Kim, Woong‐Ki; Didier, Elizabeth S.; Kuroda, Marcelo J.
Abstract : Accumulation of IM and increased monocyte turnover during SIV infection is associated with chronic pulmonary inflammation and tissue damage during disease progression. Abstract : We recently reported that increasing blood monocyte turnover that was associated with tissue macrophage death better predicts terminal disease progression in adult SIV‐infected macaques than does declining CD4 + T cell levels. To understand better mechanisms of pathogenesis, this study relates severity of lung‐tissue damage to the ratio, distribution, and inflammatory responses of lung macrophage subsets during SIV infection in rhesus macaques exhibiting varying rates of monocyte turnover. In vivo BrdU incorporation was used to evaluate kinetics of monocyte/tissue macrophage turnover. Tissue damage was scored microscopically from H&E‐stained lung‐tissue sections, and cytokine expression was examined via immunohistochemistry and confocal microscopy. Increased monocyte turnover in SIV‐infected rhesus macaques significantly correlated with severity of lung‐tissue damage, as exhibited by perivasculitis, vasculitis, interstitial pneumonia, alveolar histiocytosis, foamy macrophages, multinucleated giant cells, fibrin, and edema in the alveoli. In addition, the higher monocyte turnover correlated with declining AI ratio, increased accumulation of IM in the perivascular region of the lung, and higher expression of IL‐6 in the IM of the lung tissue exposed to a LPS, calcium ionophore, and tumor promoter combination stimulation ex vivo. Accumulation of IM associated with increasing monocyte turnover during SIV infection appears to contribute to chronic pulmonary inflammation and tissue damage during disease progression to AIDS.